7(3x-11)-2(-2x-5)+9=

Simple and best practice solution for 7(3x-11)-2(-2x-5)+9= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(3x-11)-2(-2x-5)+9= equation:


Simplifying
7(3x + -11) + -2(-2x + -5) + 9 = 0

Reorder the terms:
7(-11 + 3x) + -2(-2x + -5) + 9 = 0
(-11 * 7 + 3x * 7) + -2(-2x + -5) + 9 = 0
(-77 + 21x) + -2(-2x + -5) + 9 = 0

Reorder the terms:
-77 + 21x + -2(-5 + -2x) + 9 = 0
-77 + 21x + (-5 * -2 + -2x * -2) + 9 = 0
-77 + 21x + (10 + 4x) + 9 = 0

Reorder the terms:
-77 + 10 + 9 + 21x + 4x = 0

Combine like terms: -77 + 10 = -67
-67 + 9 + 21x + 4x = 0

Combine like terms: -67 + 9 = -58
-58 + 21x + 4x = 0

Combine like terms: 21x + 4x = 25x
-58 + 25x = 0

Solving
-58 + 25x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '58' to each side of the equation.
-58 + 58 + 25x = 0 + 58

Combine like terms: -58 + 58 = 0
0 + 25x = 0 + 58
25x = 0 + 58

Combine like terms: 0 + 58 = 58
25x = 58

Divide each side by '25'.
x = 2.32

Simplifying
x = 2.32

See similar equations:

| y=695.6+-0.6c | | 9x/10b*2xb/3x^2 | | 1-4d=-19 | | 1-14=-19 | | 45=.75x | | 5.2x+1=4.2x | | 4x^2=x^2+2 | | -4x+10=-2x-6 | | A*6+8=38 | | 9x-3y-9=0 | | 40x+30x=55 | | X^2+4x+10=-3 | | 8x^2=-40+48x | | Vc=5(0.25+e-0.24t) | | 3(x-2)=7+11 | | 9x+34=112 | | 3n-6=5n+2 | | X+81+70=180 | | 4c(x+2)=3x+11 | | 16x-(4x-2)=14 | | 6x+36=x-14 | | 2x+12=28+x | | 4x+(-2)=4x-2 | | 6y^2+42y-48=0 | | h+9.4=-9.4 | | 15x-40=7x+80 | | f(x-2)=1 | | X^2+y^2+6x-6=0 | | 0.09Xx=153.42 | | -38=-0.4k | | 3+5=3x-2 | | 3(5x+7)=-37+28 |

Equations solver categories